Harmonized system of quality assessment for electronic components. Semiconductor devices. Integrated circuits. Sectional specification for semiconductor integrated circuits excluding hybrid circuits. Internal visual examination for semiconductor integrated circuits excluding hybrid circuits. (15th August 1992) - British Standards Institution,
No abstract available